Correlating process safety leading indicators with performance. Issue 2 (8th February 2013) - Forest, Jerry J.; Kessler, Kurt
<x xml:space="preserve">Abstract</x> By definition, process safety leading indicators are predictive in nature and therefore should have a direct correlation with actual process safety incidents. This article will present Six Sigma methodologies to map the process and analyze measurements, identify leading indicators and determine where statistical correlations exist among leading indicators and actual incidents, as well as how to differentiate normal variation from an actual shift from baseline performance. The methods presented are process mapping, statistical andgraphical analysis, chi‐square test, and control charting. © 2013 American Institute of Chemical Engineers Process Saf Prog, 2013